1999
DOI: 10.1046/j.1365-2141.1999.01777.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial clustering of Langerhans cell histiocytosis

Abstract: Summary. Langerhans cell histiocytosis (LCH) is considered a non-hereditary disorder. Evaluation of the few familial cases might provide insight into its aetiology and pathogenesis. We conducted a survey to identify familial LCH cases. Data on family history, zygosity assessment in twins, clinical and laboratory features, treatment outcome, and present status were collected. According to variable con®dence for twins monozygosity assessment, we termed these pairs`presumed monozygotic' (pMZ). Nine families had m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(82 citation statements)
references
References 26 publications
2
77
0
3
Order By: Relevance
“…The disease is usually regarded as a nonhereditary disorder, but a recent report of familial clustering of LCH cases could support a role of genetic (or environmental) factor(s) in LCH (8). In a large case-control study conducted in North America, an association was found between LCH and thyroid disease as well as a family history of thyroid disease (9).…”
mentioning
confidence: 99%
“…The disease is usually regarded as a nonhereditary disorder, but a recent report of familial clustering of LCH cases could support a role of genetic (or environmental) factor(s) in LCH (8). In a large case-control study conducted in North America, an association was found between LCH and thyroid disease as well as a family history of thyroid disease (9).…”
mentioning
confidence: 99%
“…Most compelling are two independent reports demonstrating clonality of pathologic LCs (Willman et al, 1994;Yu et al, 1994). Consistent with a genetic basis for LCH, there are reports of familial clustering and a high degree of concordance among presumed monozygotic twins (Arico et al, 1999). Of course, the presence of recurrent genetic abnormalities in LCH would provide much stronger support for this idea but, because of its rarity, only a handful of surveys have been published and none of these is quite definitive.…”
Section: Etiology and Pathophysiologymentioning
confidence: 88%
“…Although the presentations in identical-twin pairs and in sporadic patients with LCH are quite disparate, the proliferating pathologic Langerhans cells share similar morphologies and molecular markers (Arico et al 1999; Badalian-Very et al 2012). Toward the center of the cytoplasm there is a folded nucleus with a prominent nuclear membrane and nucleoli.…”
Section: Discussionmentioning
confidence: 99%